Developing measures for WHO recommendations on antenatal care for a positive pregnancy experience: a conceptual framework and scoping review - Lattof, Samantha R (BMJ Open, 2019)
OBJECTIVES: In response to the newest WHO recommendations on routine antenatal care (ANC) for pregnant women and adolescent girls, this paper identifies the literature on existing ANC measures, presents a conceptual framework for quality ANC, maps existing measures to specific WHO recommendations, identifies gaps where new measures are needed to monitor the implementation and impact of routine ANC and prioritises measures for capture. METHODS: We conducted searches in four databases and five websites. Searches and application of inclusion/exclusion criteria followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses flow approach for scoping reviews. Data were extracted on measure information, methodology, methodological work and implementation. We adapted and refined a conceptual framework for routine ANC based on these measures. RESULTS: This scoping review uncovered 58 resources describing 46 existing measures that align with WHO recommendations and good clinical practices for ANC. Of the 42 WHO-recommended ANC interventions and four good clinical practices included in this scoping review, only 14 WHO-recommended interventions and three established good clinical practices could potentially be measured immediately using existing measures. Recommendations addressing the integration of ANC with allied fields are likelier to have existing measures than recommendations that focus on maternal health. When mapped to our conceptual framework, existing measures prioritise content of care and health systems; measures for girls’ and women’s experiences of care are notably lacking. Available data sources for non-existent measures are currently limited. CONCLUSION: Our research updates prior efforts to develop comprehensive measures of quality ANC and raises awareness of the need to better assess experiences of ANC. Given the inadequate number and distribution of existing ANC measures across the quality of care conceptual framework domains, new standardised measures are required to assess quality of routine ANC. Girls’ and women’s voices deserve greater acknowledgement when measuring the quality and delivery of ANC.